A VALIDATION STUDY ON NATIONAL ENGLISH EXAMINATION OF JUNIOR HIGH SCHOOL IN INDONESIA - Fiktorius, Teddy; ., Ikhsanudin; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
The research purpose is to provide feedback about the test quality from a local context that leads to the improvement of National English Examination in Indonesia. Simple random sampling is applied to obtain 1 packet of test items out of 42 packets. Next, the sample of participants as the examinees, 3 junior high schools, is obtained through stratified purposive sampling based on the school accreditation ranks. Lastly, for the sample as the content validity analysts, 3 English subject teachers are purposively selected based on the set criteria. The findings show that the test has fulfilled the criteria of having content validity. However, the test score reliability coefficient calculated with KR-21 is .65 which is categorised unreliable. The test developers need to consider revising items with very low or very high item difficulty and very low item discrimination. Finally, a further action needs to be taken to revise the implausible distractors. Keywords: National English Examination, validity, reliability, item difficulty, item discrimination, distractor Â Abstrak: Penelitian ini bertujuan untuk menghasilkan umpan balik tentang kualitas tes dari konteks lokal yang mengarah kepada peningkatan kualitas Ujian Nasional Bahasa Inggris di Indonesia. Simple random sampling digunakan untuk mendapatkan 1 dari 42 paket soal ujian. Selanjutnya, sampel peserta ujian diperoleh melalui stratified purposive sampling berdasarkan peringkat akreditasi sekolah. Kemudian, untuk sampel analis validitas isi, 3 orang guru bahasa Inggris terpilih menurut tujuan berdasarkan kriteria yang ditentukan. Hasil penelitian menyimpulkan bahwa tes tersebut memiliki validitas isi. Tetapi nilai reliabilitas yang dihitung menggunakan KR-21 adalah 0,65 sehingga dikategorikan tidak memiliki reliabilitas. Para pengembang tes perlu mempertimbangkan revisi butir soal dengan tingkat kesukaran yang sangat rendah atau sangat tinggi dan butir soal dengan daya pembeda yang sangat rendah. Akhirnya, tindak lanjut perlu diambil untuk merevisi pengecoh yang tidak berfungi dengan baik. Kata kunci: Ujian Nasional Bahasa Inggris, validitas, reliabilitas, tingkat kesukaran, daya pembeda, pengecoh